2022
DOI: 10.3390/ph15080908
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Chronic Low-Dose Soluble Epoxide Hydrolase and Acetylcholinesterase Pharmacological Inhibition Promotes Memory Reinstatement in Alzheimer’s Disease Mice Models

Abstract: Alzheimer’s disease (AD) is a progressive neurological disorder with multifactorial and heterogeneous causes. AD involves several etiopathogenic mechanisms such as aberrant protein accumulation, neurotransmitter deficits, synaptic dysfunction and neuroinflammation, which lead to cognitive decline. Unfortunately, the currently available anti-AD drugs only alleviate the symptoms temporarily and provide a limited therapeutic effect. Thus, new therapeutic strategies, including multitarget approaches, are urgently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…The sex of the mice studied was not specified; therefore, it is not possible to compare our sex differences findings to these results. Others have demonstrated that various sEHI compounds improve memory as measured by other cognitive function tests in the context of multiple disease models; however, these studies either only studied males, or combined males and females into one group [35][36][37][80][81][82][83][84][85]. Therefore, to our knowledge, our study is the first to describe sex differences in the effects of sEHI on murine behavior and memory.…”
Section: Sex Differences In the Cognitive And Behavioral Outcomes Wit...mentioning
confidence: 85%
See 2 more Smart Citations
“…The sex of the mice studied was not specified; therefore, it is not possible to compare our sex differences findings to these results. Others have demonstrated that various sEHI compounds improve memory as measured by other cognitive function tests in the context of multiple disease models; however, these studies either only studied males, or combined males and females into one group [35][36][37][80][81][82][83][84][85]. Therefore, to our knowledge, our study is the first to describe sex differences in the effects of sEHI on murine behavior and memory.…”
Section: Sex Differences In the Cognitive And Behavioral Outcomes Wit...mentioning
confidence: 85%
“…Oxylipins are bioactive products of PUFA oxidation and have been demonstrated to play a role in neurological function, neuroinflammation, and neurodegenerative diseases, including dementias [8,11,12]. In addition, inhibition of sEH has been investigated as a potential therapeutic target for a wide range of neurological disorders, including dementias [13,21,22,26,30,31,[34][35][36][37]. Therefore, the impact of sEHI on the comprehensive profile of oxylipins is an important area of study to further understand how this treatment might be beneficial in neurodegenerative diseases such as dementia, a major global killer of men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation